2008
DOI: 10.3758/brm.40.1.347
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of a palm-based psychomotor vigilance task to severe sleep loss

Abstract: In this study, we evaluated the sensitivity of a 5-min personal digital assistant-psychomotor vigilance test (PDA-PVT) to severe sleep loss. Twenty-one participants completed a 10-min PVT-l92 and a 5-min PDA-PVT at two hourly intervals during 62 h of sustained wakefulness. For both tasks, response speed and number of lapses (RTs > 500) per minute significantly increased with increasing hours of wakefulness. Overall, standardized response speed scores on the 5-min PDA-PVT closely tracked those of the PVT-192; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…One concern about the s2P tool was its shorter duration (3 min in this study), as compared to the standard, 10-min RT tests that have usually been reported in previous research Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005). This choice of a shorter duration was deliberate, to address many critiques that the 10-min PVT is impractically long for many contexts Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005). The duration of an alertness test is crucial, since even severely sleep-deprived individuals will be able to compensate by increasing effort, which will result in adequate performance.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…One concern about the s2P tool was its shorter duration (3 min in this study), as compared to the standard, 10-min RT tests that have usually been reported in previous research Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005). This choice of a shorter duration was deliberate, to address many critiques that the 10-min PVT is impractically long for many contexts Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005). The duration of an alertness test is crucial, since even severely sleep-deprived individuals will be able to compensate by increasing effort, which will result in adequate performance.…”
Section: Discussionmentioning
confidence: 97%
“…The results indicated that s2P is a valid tool for differentiating alert from sleepy states in the same individual, and that this tool is just as sensitive as the classic PVT to track fatigue-related changes during extended wakefulness and sleep loss conditions. One concern about the s2P tool was its shorter duration (3 min in this study), as compared to the standard, 10-min RT tests that have usually been reported in previous research Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005). This choice of a shorter duration was deliberate, to address many critiques that the 10-min PVT is impractically long for many contexts Basner & Rubinstein, 2011;Lamond et al, 2005Lamond et al, , 2008Roach et al, 2006;Thorne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations